2006
DOI: 10.1084/jem.20052272
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lymph node vascular growth by dendritic cells

Abstract: Lymph nodes grow rapidly and robustly at the initiation of an immune response, and this growth is accompanied by growth of the blood vessels. Although the vessels are critical for supplying nutrients and for controlling cell trafficking, the regulation of lymph node vascular growth is not well understood. We show that lymph node endothelial cells begin to proliferate within 2 d of immunization and undergo a corresponding expansion in cell numbers. Endothelial cell proliferation is dependent on CD11c+ dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
286
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(309 citation statements)
references
References 58 publications
21
286
1
1
Order By: Relevance
“…Other studies have suggested that the growth of HEVs is associated with increased lymphocyte entry into the LNs, which, again, boosts the immune responses (30,31). These findings led us to speculate that the increase in lymphangiogenesis and the growth of HEVs within LNs might stimulate immune responses in CD19 Cre /hVEGF-A fl mice.…”
Section: Immunosuppressive Roles Of Vegf-amentioning
confidence: 83%
“…Other studies have suggested that the growth of HEVs is associated with increased lymphocyte entry into the LNs, which, again, boosts the immune responses (30,31). These findings led us to speculate that the increase in lymphangiogenesis and the growth of HEVs within LNs might stimulate immune responses in CD19 Cre /hVEGF-A fl mice.…”
Section: Immunosuppressive Roles Of Vegf-amentioning
confidence: 83%
“…In the steady state, as much as 50% of recirculating lymphocytes passing through an LN exit through the efferent lymph (5). During inflammation, LN activation triggers remodeling of high endothelial venules (HEVs) to increase lymphocyte entry by manyfold (11,12). Undesirable situations, including LN hypertrophy and hyperactivation, which are often associated with autoimmune and chronic inflammatory diseases, may arise if these lymphocytes fail to leave the inflamed LNs in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies indicated that plasticity in LN structural organization continues to exist throughout life, particularly during inflammation and infection (8,9). Reorganization of LN microanatomy during inflammation is characterized by the remodeling and expansion of key LN stromal cells, including lymphatic endothelial cells (LECs) (10), blood endothelial cells (BECs) (11,12), and fibroblastic reticular cells (FRCs) (13,14). Importantly, increasing evidence reveal the immunological significance of the remodeling of these stromal elements.…”
mentioning
confidence: 99%
“…In addition, lymphotoxin signaling may also indirectly affect FRC turnover, because LTbR blockade severely attenuated BEC expansion in LTbR-Ig-treated mice. It is noteworthy that LTbR plays an important role in remodeling (28)(29)(30) and in the functional maintenance (24) of high endothelial venules (HEVs). Long-term LTbRIg treatment causes a loss of HEV phenotype (24), resulting in the impaired recruitment of lymphocytes into reactive LNs during the ongoing immune response.…”
Section: Discussionmentioning
confidence: 99%